Polissemias da desigualdade no Livro V das Ordenações Filipinas: O escravo integrado - Ferreira, Ricardo Alexandre [UNESP] (FapUNIFESP (SciELO), 2015)
This article aims to discuss one of the central points of criticism levelled by different members of the so-called Enlightenment movement to the Ancien Régime's world. This notion, namely «inequality under the law», was already debated and explored by specialized historiography,and is understood as an intrinsic and negative attribute of different European states until the end of XVIIIth century. It is assumed that is essential to the historian interested in the justice form's study the understanding of the meanings given to many concepts and legal status. Such ideas must be considered within the limits of time and place in which they were developed and used by their contemporaries. Specifically, it is intended to take a closer look of the legal procedures presented in the Book V of the Philippine Code, or Ordinances and Laws of the Kingdom of Portugal, a 1603 compilation of laws that remained, in Brazil, largely observed until 1830. From such analyses, a study of ambivalence and simultaneities of meaning present in the sentences imposed on people of different qualities or conditions, between the seventeenth and eighteenth centuries, will be conducted. To conclude, a special focus on punishments destined exclusively to slaves, considered both as things and people, will be given.
Inequalities polysemy in the Book V of the Philippine ordinances: The integrated slave
Keywords: Justice; Ordinances; Portugal; Slavery